Analysis of Tim-3 as a therapeutic target in prostate cancer - Yongrui Piao; Xuanshun Jin (Tumor Biology)
Tim-3 (T-cell immunoglobulin domain and mucin domain–containing molecule 3) is a newly discovered immunomodulatory protein, which plays an important role in immunity regulation. Recent evidence suggests that Tim-3 is differentially regulated in a variety of tumors and has potential as a therapeutic target. The aim of this study was to investigate the effect of Tim-3 on the development of prostate cancer. Tim-3 expressing on peripheral CD4+ T and CD8+ T cells was analyzed by flow cytometry. The relationships between Tim-3 expression and clinicopathological features were analyzed. Immunohistochemical expression of Tim-3 was examined in our large numbers of paraffin-fixed prostate tissues. Flow cytometry revealed that expression of Tim-3 was significantly increased on both CD4+ and CD8+ T cells in prostate cancer patients than that in benign prostate hyperplasia patients. Also, the level of Tim-3 on CD4+ T cells was positively correlated with CD8+ T cells in patients. Further analyses revealed that the levels of Tim-3 on CD4+ T cells and CD8+ T cells exhibited different expression patterns in terms of localization depending on pathological category of prostate cancer and metastasis. Immunohistochemical analysis revealed that positive staining of Tim-3 in prostate cancer but little or no staining of Tim-3 was observed in benign prostate hyperplasia epithelium. Tim-3 may affect the development and progression of prostate cancer, which may provide knowledge for using Tim-3 as a novel therapy for effective prostate cancer management.